2013
DOI: 10.1262/jrd.2013-003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Downregulating Oct-4 Transcript by RNA Interference on Early Development of Porcine Embryos

Abstract: The objective of this study was to investigate the role of the POU family transcription factor, Oct-4, in the early development of porcine embryos. We attempted Oct-4 downregulation of porcine early embryos by RNA interference, and evaluated Oct-4 suppression of developmental competencies and gene transcripts in porcine embryos. Injection of specific siRNA resulted in a distinct decrease in Oct-4 mRNA and protein expression in porcine embryos until at least the morula stage. Although the porcine embryos inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…In porcine embryos derived from IVF, OCT-4 is required for embryonic development from the morula to the blastocyst stage [5]. In this study, OCT-4 downregulation inhibited the transformation of morula to blastocyst in porcine embryos derived by parthenogenetic treatment.…”
Section: Discussionmentioning
confidence: 57%
“…In porcine embryos derived from IVF, OCT-4 is required for embryonic development from the morula to the blastocyst stage [5]. In this study, OCT-4 downregulation inhibited the transformation of morula to blastocyst in porcine embryos derived by parthenogenetic treatment.…”
Section: Discussionmentioning
confidence: 57%
“…is essential for porcine TE segregation (Emura et al, 2016;Sakurai et al, 2013). Therefore, OCT-4 functions in the formation of both ICM and TE in porcine embryos.…”
Section: Yap1 and Lats2 Knockdown In Porcine Embryosmentioning
confidence: 99%
“…Moreover, there are evidences for differences in molecular mechanisms of the ICM/TE segregation between mice and pigs. For example, our previous report has demonstrated that OCT-4 is essential for both ICM and TE segregation in porcine embryos, while it is needed only for ICM formation in mice (Emura et al, 2016;Nichols et al, 1998;Sakurai et al, 2013). In addition, CDX2 is dispensable for blastocyst formation in porcine embryos, but not in murine embryos (Bou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies using mouse embryos, knockout or of OCT4 itself did not impair early blastocyst formation [40, 44] although formation of the inner cell mass and its pluripotency were impaired [25]. To test targeting efficiency of the porcine OCT4 gene, we chose exons 2 and 5 and selected two target regions to introduce indels via non-homologous end repair(NHEJ), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%